2006
DOI: 10.1002/jlcr.1110
|View full text |Cite
|
Sign up to set email alerts
|

Development of a reliable remote-controlled synthesis ofβ-[11C]-5-hydroxy-L-tryptophan on a Zymark robotic system

Abstract: SummaryPrecise staging of neuroendocrine tumors (NET) using positron emission tomography (PET) tracers visualizing their specific metabolic activity is of interest. Besides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…[ 18 F]FDOPA at 0.19 F 0.01 mL, corresponding to a dose of 6.17 F 0.63 MBq, was injected per animal. [ 11 C]HTP was synthesized via an enzymatic method with an average specific activity of 30,000 GBq/mmol after end of synthesis as recently described (16). It was used at a concentration of f0.67 nmol/mL.…”
Section: Methodsmentioning
confidence: 99%
“…[ 18 F]FDOPA at 0.19 F 0.01 mL, corresponding to a dose of 6.17 F 0.63 MBq, was injected per animal. [ 11 C]HTP was synthesized via an enzymatic method with an average specific activity of 30,000 GBq/mmol after end of synthesis as recently described (16). It was used at a concentration of f0.67 nmol/mL.…”
Section: Methodsmentioning
confidence: 99%
“…As outlined above, more research has been done with [ 11 C]AMT than with [ 11 C]5-HTP, probably because producing [ 11 C]5-HTP is difficult, requiring several enzymatic steps [ 110 ]. At the moment it is only produced in four to five centres all over the world.…”
Section: Discussionmentioning
confidence: 99%
“…Tracer and Drug Treatment [ 11 C]5-HTP was produced according to a published method. 22 The average injected dose of [ 11 C]5-HTP was 12.0 ± 6.4 MBq with a specific radioactivity of 23.4±11.2 GBq/mmoL. All drugs were administered by i.p.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…Another option to measure 5-HT synthesis with PET, is labeling the endogenous precursor of serotonin, [ 11 C]5-HTP. 21,22 A great advantage of this compound is that it is metabolized exactly in the same way as endogenous 5-HTP. Several studies with [ 11 C]5-HTP have indicated that this tracer can be used to measure 5-HT synthesis rates by kinetic modeling of PET data.…”
Section: Introductionmentioning
confidence: 99%